Function of Macrophages in Disease: Current Understanding on Molecular Mechanisms - Zhang, Chunye; Yang, Ming; Ericsson, Aaron C. (Frontiers in Immunology, 2021)
Tissue-resident macrophages (TRMs) are heterogeneous populations originating either from monocytes or embryonic progenitors, and distribute in lymphoid and non-lymphoid tissues. TRMs play diverse roles in many physiological processes, including metabolic function, clearance of cellular debris, and tissue remodeling and defense. Macrophages can be polarized to different functional phenotypes depending on their origin and tissue microenvironment. Specific macrophage subpopulations are associated with disease progression. In studies of fate-mapping and single-cell RNA sequencing methodologies, several critical molecules have been identified to induce the change of macrophage function. These molecules are potential markers for diagnosis and selective targets for novel macrophage-mediated treatment. In this review, we discuss some of the recent findings regarding less-known molecules and new functions of well-known molecules. Understanding the mechanisms of these molecules in macrophages has the potential to yield new macrophage-mediated treatments or diagnostic approaches to disease.